Optimalisasi Stimulasi Motorik Halus sebagai Kegiatan Pra Menulis Anak Usia Dini dengan kecenderungan Disgrafia - Falera, Ana (Efektor, 2024)
This study aims to explore the optimization of fine motor stimulation as a pre-writing activity in early childhood with a tendency towards dysgraphia, a developmental disorder that affects writing ability. Dysgraphia often hinders children's development in academic skills, especially in the writing process. This study was conducted through a literature study method that analyzed literature related to fine motor development that is relevant to children with dysgraphia. The results of the study showed that appropriate fine motor stimulation, such as beading, cutting, and tracing pattern activities, can significantly improve visual-motor coordination and fine muscle control needed in writing. In addition, structured interventions help improve the quality of children's handwriting, such as consistency of letter size, spacing between letters, and pencil pressure. This stimulation program also has a positive impact on children's self-confidence in carrying out writing activities. The conclusion of this study is that optimizing fine motor stimulation plays an important role in preparing early childhood with a tendency towards dysgraphia to develop better writing skills. However, this intervention requires active involvement from teachers and parents and needs to be adjusted to the child's individual needs. With the right support, children with dysgraphia can overcome writing difficulties and improve their academic readiness.